PREPARATION AND ACCEPTABILITY OF THE CONVENTIONAL AND LIGHT MANA CUBIU JELLY - Furlaneto, Karina Aparecida [UNESP]; Ramos, Juliana Arruda [UNESP]; Daiuto, Erica Regina [UNESP]; Vieites, Rogerio Lopes [UNESP]; Carvalho, Lidia Raquel de [UNESP] (Univ Federal Mato Grosso, 2015)
The objective of this study was to develop and evaluate the sensory light jelly of mana cubiu formulated with different concentrations of sucralose. Fruit mana cubiu were used, purchased from a commercial production, in Sao Paulo, the region of Vale do Ribeira. The fruits were washed, sanitized with sodium hypochlorite followed by rinse, peel and seed the withdrawal. Bleaching was carried out at 90 degrees C for 5 minutes and triturated in industrial blender. The pulp was packed in polyethylene bags and stored in freezer for later development of jelly. The jams were prepared with a concentration of 60: 40 (pulp crystallized sugar) for conventional and 60:40 (pulp: Crystal sugar + Sucralose) for light jellies. For gelation thereof occur, citrus pectin was used. The jelly was the bottled hot in glass containers with a capacity of 320g, pre-sterilized closed and inverted. After filling the jellies were naturally cooled and stored at room temperature. In the jellies was taken microbiological and sensory analysis for the storage period of 120 days. Analysis of variance was performed in a completely randomized design, factorial design with two factors, followed by Tukey's test (1% probability) for multiple comparisons. The results of the jams did not present any microbiological contamination until 120 days of storage, appearing in satisfactory sanitary conditions. The Light version 2, whose proportions were 60% pulp + 28% sucrose + 12% sucralose, it was the more accepts for the appraised sensorial attributes and for purchase intention.
Keywords: Solanum sessiliflorum Dunal; processing; sensorial analyse; sucralose